Viability of Deficit Irrigation Pre-Exposure in Adapting Robusta Coffee to Drought Stress - Sseremba, G.; Tongoona, P.B.; Musoli, P.; et al. (Agronomy, 2023)
Coffea canephora has high but inadequately exploited genetic diversity. This diversity, if well exploited, can sustain coffee productivity amidst climate change effects. Drought and heat stress are major global threats to coffee productivity, quality, and tradable volumes. It is not well understood if there is a selectable variation for drought stress tolerance in Robusta coffee half-sibs as a result of watering deficit pre-exposure at the germination stage. Half-sib seeds from selected commercial clones (KR5, KR6, KR7) and a pipeline clone X1 were primed with deficit watering at two growth stages followed by recovery and later evaluated for tolerance to watering deficit stress in three different temperature environments by estimation of plant growth and wilt parameters. Overall, the KR7 family performed the best in terms of the number of individuals excelling for tolerance to deficit watering. In order of decreasing tolerance, the 10 most promising individuals for drought and heat tolerance were identified as: 14.KR7.2, 25.X1.1, 35.KR5.5, 36.KR5.6, 41.KR7.5, 46.KR6.4, 47.KR6.5, 291.X1.3, 318.X1.3, and 15.KR7.3. This is the first prospect into the potential of C. canephora half-sibs’ diversity as an unbound source of genetic variation for abiotic stress tolerance breeding.
Research Article
Keywords: Coffea canephora; climate change adaptation; drought tolerance